Utilizing Digital Diplomacy in the Israeli Discourse to Influence Arab Public Opinion during the Israeli Aggression on Gaza 2021 - Izzeddin Khaled Alrantisi; Ihab Ahmad Awais; Wesam Almahallawi; Norhayati Rafida Abdul Rahim (Sciendo fait partie de la société De Gruyter, 2024)
Non-Indexed Publication